Mesoporous Cobalt Oxide (CoOx) Nanowires with Different Aspect Ratios for High Performance Hybrid Supercapacitors - Haomin Ji; Yifei Ma; Zhuo Cai; Micun Yun; Jiemin Han; Zhaomin Tong; Mei Wang; Jonghwan Suhr; Liantuan Xiao; Suotang Jia; Xuyuan Chen (Nanomaterials, 2023)
Cobalt oxide (CoOx) nanowires have been broadly explored as advanced pseudocapacitive materials owing to their impressive theoretical gravimetric capacity. However, the traditional method of compositing with conductive nanoparticles to improve their poor conductivity will unpredictably lead to a decrease in actual capacity. The amelioration of the aspect ratio of the CoOx nanowires may affect the pathway of electron conduction and ion diffusion, thereby improving the electrochemical performances. Here, CoOx nanowires with various aspect ratios were synthesized by controlling hydrothermal temperature, and the CoOx electrodes achieve a high gravimetric specific capacity (1424.8 C g−1) and rate performance (38% retention at 100 A g−1 compared to 1 A g−1). Hybrid supercapacitors (HSCs) based on activated carbon anode reach an exceptional specific energy of 61.8 Wh kg−1 and excellent cyclic performance (92.72% retention, 5000 cycles at 5 A g−1). The CoOx nanowires exhibit great promise as a favorable cathode material in the field of high-performance supercapacitors (SCs).